Strategic Management of Teacher Professional Competence Development: A Multi-Site Case Study in State Schools - M. Sukron Suwarno Sundoro; Abdul Majid (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
While teacher professional competence is the core driver of educational quality, its effective management across different schooling levels remains a complex challenge. This study aims to explore and compare the strategic management of teacher professional competence development. Utilizing a qualitative multi-site comparative case study, data were collected through participant observation, in-depth interviews, and document analysis at SMPN 1 Kraton (Junior High) and SDN Gerongan (Elementary). The findings reveal divergent yet effective approaches: SMPN 1 Kraton employs an external expansion strategy, utilizing formal external forums, financial incentives, and technology-assisted supervision. Conversely, SDN Gerongan focuses on internal standardization, leveraging in-house peer mentoring and symbolic recognition to build a highly disciplined professional culture. Both institutions rely heavily on proactive leadership and adequate physical infrastructure to navigate external disruptions. In conclusion, effective competence management requires aligning coaching strategies with the specific pedagogical demands of the educational tier. This research contributes an adaptive, cross-level strategic management model that institutional leaders can replicate to systematically elevate teacher professionalism in basic education.